Pengaruh Penilaian Kinerja Terhadap Pengembangan Karier Pada Kantor Camat Atinggola Kabupaten Gorontalo Utara - Syaiful Pakaya (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2022)
This study aims to determine the significance of the effect of performance appraisal on career development at the Atinggola District Office, North Gorontalo Regency. This study used a sample of 31 respondents, the questionnaire was used as the main data collection tool, and hypothesis testing was analyzed using regression analysis. Based on the results of the study, it is shown that the hypothesis that performance appraisal has a positive and significant effect on employee career development is proven by the regression coefficient value. The contribution given by the performance appraisal variable to career development is 0.537 or 53.7%, that if the performance appraisal variable increases by one unit, career development (Y) increases by 0.537. From the processed data, it can be seen that the coefficient of determination is r2 = 0.695. This value means that 69.5% of the independent variable X can explain the dependent variable Y and 30.5% is explained by other variables, or in other words that the contribution of the independent variable, namely performance appraisal to career development, is 69.5% while the rest is 30.5% is influenced by other variables not included in this study.